Biocontrole da mancha e murcha bacteriana do tomateiro por bactérias endofíticas - Godinho, Moysa Carvalho (2018)
The diseases of bacterial etiology are among the main factors that affect tomato productivity, i. e., the bacterial spot(Xanthomonas vesicatoria, X. euvesicatoria, X. gardneri and X. perforans) and bacterial wilt (Ralstonia solanacearum). The control of bacteria is difficult in environments ideal for the development of diseases, through the application of copper products and the use of resistant varieties, which are sometimes earlier broken by the pathogen. Therefore, biological control becomes a promising alternative capable of reducing the severity of diseases. The aims of this work were to evaluate the endophytic isolates in the control in vitro and in vivo, against the species of the complex Xanthomonas vesicatoria and Ralstonia solanacearum, in tomato. Five isolates of endophytic bacteria were tested for the control of bacterial spot in the in vitro test, UFLA 285, 22 and 07. In the greenhouse tests, the results varied depending of each type of Xanthomonas complex. X. euvesicatoria, decreased the severity by 85.76% and 85%. X. gardneri, four isolates was more effective, with control percentages corresponding to 73.10%, 68.55%, 65.13% and 64.97%.X. perforans, the most effective isolate was UFLA 45, with a 62.65% severity reduction.X. vesicatoria, isolates reduced the severity in 82.13%, 65.39% and 63.29%. Fifteen endophytic isolates were selected for the bacterial wilt. As for the antagonism test, eight isolateswas able to inhibit the in vitro growth of R. solanacearum. Of these, UFLA - 22, 285, 50, 51, 40 and 47 were the most effective. To the in house experiment of vegetation, two methods of inoculation were evaluated: immersion of the roots tomato seedlings 'Santa Clara' cultivar and inoculation via soil irrigation. The method of immersion was more severe, however, the isolates managed to control the disease in 66.66% and 65.52%, differing statistically from the control treatment (100% disease). For the irrigation method, UFLA 06 was the most effective, controlling 65.02% of the disease in relation to the control, concluding that endophyticsbacterials have potential for biocontrol over the species belonging to the genus Xanthomonas. and bacterial wilt disease both in vitro and in greenhouse.